2014
DOI: 10.1177/0954407014521177
|View full text |Cite
|
Sign up to set email alerts
|

Mode shift control for a dual-mode power-split-type hybrid electric vehicle

Abstract: This paper presents a mode shift control algorithm for reducing the variation in the driveshaft torque for a dual-mode power-split-type hybrid electric vehicle. To evaluate the shift characteristics of this hybrid electric vehicle, dynamic models for the hybrid electric vehicle powertrain were developed. Using the dynamic models, a mode shift performance simulator was developed, and simulations were performed. To analyse the shift characteristics during the mode shift, bond-graph models for the transient state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Once the control executions of each SRT for all modes are determined in Step 2, the next step is to determine the mode shift during drive cycles [31]. Dynamic programming is used to obtain optimal mode shift and to ensure the state of charge (SOC) sustaining.…”
Section: Discretization Of the Target Cyclementioning
confidence: 99%
“…Once the control executions of each SRT for all modes are determined in Step 2, the next step is to determine the mode shift during drive cycles [31]. Dynamic programming is used to obtain optimal mode shift and to ensure the state of charge (SOC) sustaining.…”
Section: Discretization Of the Target Cyclementioning
confidence: 99%
“…Hong et al. 17 presented a mode transition control algorithm for reducing driveshaft torque variation for a dual-mode PS HEV, where the motor compensation torque is calculated from wheel transient torque. By simulation and experiments, it is shown that the motor torque compensation is effective in stabilization of output torque and reduction of vehicle jerks.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al 11 proposed a brake-assisted coordinated control strategy to mitigate the driveline speed oscillations while cranking the engine quickly. To reduce the variation in the driveshaft torque, Hong et al 12 proposed a mode shift control to compensate for the variation of transient torque. Zhu et al 13 adopted a fuzzy gain-scheduling PID controller to reduce mode transition duration, vehicle jerk, and frictional losses of the clutch.…”
Section: Introductionmentioning
confidence: 99%